The use of a Scorecard to Evaluate the Public’s Comprehension of COVID-19: A Pilot Study - Kalanjati, Viskasari Pintoko; Hasanatuludhhiyah, Nurina; d'Arqom, Annette; Arsyi, Danial Habri; Permana, Putu Bagus Dharma; Pratiwi, Octaviana Galuh; Farabi, Moh. Reza; Susila, I Made Dwi Yudiartana Putra; Yudhono, Anggit Satriyo; Brilianti, Natasya Nurvita (Jurnal Keperawatan Soedirman, 2022)
The rapid spread of information and infodemic might result in public confusion and hinder the handling of the COVID-19 pandemic. Public comprehension of COVID-19 as part of health literacy is an important determinant to filter hoaxes from facts. Therefore, a scoring card called the Karlivid (the COVID-19 literacy and public vaccination scorecard) was developed to evaluate the individual’s comprehension level of COVID-19. A pilot study was conducted with this scoring card. The participants were recruited via consecutive random sampling by using emails from the researcher’s contact list (n=92). A total of 78.3% of the respondents were considered to have an adequate comprehension level. Approximately 77% of all respondents agreed that this card could help them know their comprehension level, 81.5% agreed that this card could improve their comprehension, 81.5% agreed that the items in this card could help them screen facts from hoaxes, and 81.5% agreed that the language used was easily understood by the laypersons. Therefore, the Karlivid is a valid and reliable scorecard that can be used to evaluate public comprehension of COVID-19. Most of the respondents also had a good level of comprehension of this assigned topic